Composite brake disc with friction layer and preparation method of composite brake disc

By adjusting the size of silicon carbide grains in the friction layer of the carbon ceramic composite brake disc, optimizing the density and width of cracks, the friction layer peeling problem caused by uneven cracks in the existing brake disc is solved, and the wear resistance of the brake disc is improved and frictional properties.

CN119412451AActive Publication Date: 2025-02-11深圳市佰斯倍新材料科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411341192.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-11
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The area size and width of cracks surrounded by adjacent cracks in the existing carbon ceramic composite brake discs in the friction layer are uneven, resulting in the friction layer being easily peeled and affecting the brake performance.

Method used

By controlling the size of silicon carbide grains added in the friction layer, adjust the density and crack gap size of cracks, and optimize the distribution density and width of cracks to improve the overall performance of the brake disc.

Benefits of technology

By optimizing the crack structure, the wear resistance and friction performance of the brake disc are improved, the peeling of the friction layer is reduced, and the quality and performance of the brake disc are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059746450000021
    Figure BDA0005059746450000021
  • Figure BDA0005059746450000051
    Figure BDA0005059746450000051
  • Figure BDA0005059746450000141
    Figure BDA0005059746450000141
Patent Text Reader

Abstract

The invention provides a composite brake disc with a friction layer, the composite brake disc with the friction layer comprises a base body layer and the friction layer, the friction layer is arranged on the outer surface of the base body layer, and the friction layer comprises 60-95% of silicon carbide, 5-40% of silicon and 0-5% of carbon; irregular cracks are distributed on the surface of the friction layer, adjacent cracks are communicated with each other to form a crack unit, the average longest distance of the crack units in the plane direction is 3-7 mm, and the average width of the crack units perpendicular to the longest direction is 2.5-6.5 mm. The size and proportion of silicon carbide grains added in the friction layer are controlled, the density of cracks and the size of crack gaps are adjusted, the optimal ratio relation between the crack width and the crack distribution density is formed, and great significance is achieved for improving the crack state and improving the abrasion resistance of the brake disc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brake disc manufacturing, and in particular to a composite brake disc with a friction layer and a preparation method thereof. Background Art

[0002] Brake discs are mainly used to slow down or stop cars in an emergency. They are particularly important because they are related to human life safety in emergencies. Since braking will produce a short-term large impact friction and generate a large amount of heat energy, the material of the brake disc should have properties such as heat resistance, impact resistance, fatigue resistance, and high strength. Carbon-ceramic composite materials (i.e., C / SiC composite materials, including carbon-carbon silicon-infiltrated modified silicon carbide composite materials, i.e., C / C-SiC composite materials, collectively referred to as carbon-ceramic composite materials) are developing rapidly, and their application has been expanded to the field of automotive brakes on a large scale. Compared with the existing gray cast iron brake discs and carbon-carbon composite brake discs on the market, carbon-ceramic composite brake discs have the advantages of light weight, excellent high-temperature friction performance, and wear resistance.

[0003] At present, the preparation process of carbon ceramic brake disc is needle puncture-carbonization-high temperature treatment-chemical vapor deposition-high temperature treatment-application of friction layer-processing-siliconization-processing. Due to the high content of silicon carbide in the friction layer, cracks will be generated due to the difference in thermal expansion coefficient between the friction layer and the carbon ceramic matrix. The cracks formed in the friction layer prepared by the current process are uneven in size, and the width of the cut crack itself is wide, which makes it easy for the friction layer to peel off during the wear test. In this regard, a composite brake disc with a friction layer is proposed, and the size of the area surrounded by adjacent cracks in the friction layer and the crack width are optimized. Summary of the invention

[0004] The present invention aims to provide a composite brake disc with a friction layer, by controlling the size of silicon carbide grains added in the friction layer to adjust the density of cracks and the size of crack gaps, thereby further improving the comprehensive performance of the brake disc.

[0005] To achieve this purpose, the present invention provides a composite brake disc with a friction layer, the composite brake disc with a friction layer comprises a base layer and a friction layer, the friction layer is arranged on the outer surface of the base layer, and the friction layer comprises 60-95% silicon carbide, 5-40% silicon and 0-5% carbon. Irregular cracks are distributed on the surface of the friction layer, and adjacent cracks are interconnected to form crack units, the average longest distance of the crack units in the plane direction is 3-7mm, and the average width of the crack units perpendicular to the longest direction is 2.5-6.5mm. The crack distribution density ρ of the friction layer in any direction of the brake disc diameter and the crack width w satisfy the following formula:

[0006]

[0007] Wherein, ρ = n / L, n is the number of cracks passing through the length L in any direction, L is the radius of the brake disc, and α is the relationship coefficient, which can be any value between 2 and 8. α can be an integer or a decimal.

[0008] Preferably, the silicon carbide in the friction layer includes first silicon carbide particles, second silicon carbide particles and third silicon carbide particles, the first silicon carbide particles have a particle size of 80-120 μm, the second silicon carbide particles have a particle size of 5-30 μm, and the third silicon carbide particles have a particle size of less than 5 μm.

[0009] Preferably, the first silicon carbide particle content is 45-65% of the silicon carbide content, the second silicon carbide particle content is 20-40% of the silicon carbide content, and the third silicon carbide particle content is 10-20% of the silicon carbide content.

[0010] Preferably, the average area of ​​the crack unit is 15-45 mm 2 .

[0011] Preferably, the matrix layer comprises 30-50% carbon fiber, 40-65% silicon carbide and 5-15% silicon.

[0012] The present invention also provides a method for preparing a composite brake disc having a friction layer, which is used to prepare the composite brake disc having a friction layer, comprising the following steps:

[0013] S1: preparing a carbon fiber preform of a predetermined thickness;

[0014] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body;

[0015] S3: Carbonizing the impregnated body to obtain a carbonized body, the carbonization temperature is 800-1100° C., and the temperature is kept for 4-6 hours;

[0016] S4: applying phenolic slurry containing silicon carbide powder on the carbonized body, and then drying to obtain a second body, wherein a prefabricated friction layer is formed on the surface of the second body, and the thickness of the prefabricated friction layer is 1-3 mm;

[0017] S5: subjecting the second green body to low-temperature graphitization treatment in nitrogen to obtain a graphitized green body;

[0018] S6: Mechanically processing the graphitized body to obtain a brake disc body;

[0019] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600-1700°C, the holding time is 2-4h, and the furnace pressure is less than 1000Pa;

[0020] S8: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the composite brake disc with the friction layer.

[0021] Preferably, the method for preparing the carbon fiber preform is as follows: stacking the carbon fiber unidirectional cloth and the carbon fiber mesh as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloths of two adjacent unit layers are at an angle of 90°, and after stacking one unit, acupuncture the sample, and repeat the above process to obtain a carbon fiber preform of the desired thickness, wherein the acupuncture density is 50-200 needles / cm 2 .

[0022] Preferably, the steps S2 and S3 are performed at least once to make the density of the carbonized body reach 1.25-1.45 g / cm 3 .

[0023] Preferably, the phenolic slurry comprises a silicon carbide particle concentration of 10-30wt%, a phenolic content of 5-25wt%, and an alcohol content of 50-85wt%; the particle size of the silicon carbide particles ranges from 20-150μm.

[0024] Preferably, the low-temperature graphitization treatment temperature is 1400-1800° C., and the insulation time is 2 hours.

[0025] Beneficial effects: The composite brake disc with a friction layer provided by the present invention is easy to crack due to thermal mismatch when siliconizing is finished and cooled. According to the generated crack width and crack distribution density, an optimal ratio relationship is formed, which provides a judgment standard for the qualification of the brake disc and helps to adjust the process parameters in the production process to improve the quality and performance of the brake disc. The present invention also proposes to control the size and proportion of silicon carbide grains added in the friction layer, and the density of cracks and the size of crack gaps can be adjusted. When siliconizing is finished and cooled, the coarser the silicon carbide particles are, the lower the mechanical properties of the friction layer are, and cracks are prone to occur due to thermal mismatch. Therefore, the size of the surface crack unit formed is small, the crack gap is narrow, and the wear debris is not easy to accumulate at the crack gap during friction, so the wear and peeling situation is greatly reduced, and the wear resistance of coarse silicon carbide is better than that of fine silicon carbide. However, only 80-120 microns of coarse silicon carbide is added, the initial silicon carbide overlap points are insufficient, the bonding strength between silicon carbide particles is seriously reduced, and the coarse silicon carbide particles are easily caused to peel off, resulting in unstable friction coefficient and increased wear. By adding some smaller 5-30μm silicon carbide to the 80-120μm coarse silicon carbide, there will be more overlapping points between the silicon carbide particles. The silicon carbide generated by the reaction of carbon and silicon during siliconization can better connect the initial silicon carbide together to form a silicon carbide skeleton with a certain strength. By rationally selecting silicon carbide particles of different particle sizes and adjusting their proportions, it is of great significance to improve the crack state and enhance the wear resistance of the brake disc.

[0026] The present invention also provides a method for preparing a composite brake disc with a friction layer. The entire preparation process is simple, adopts low-temperature graphite conversion, has low process difficulty, and is easy to mass produce. DETAILED DESCRIPTION

[0027] The embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] This embodiment provides a composite brake disc with a friction layer, the composite brake disc with a friction layer comprises a base layer and a friction layer, the friction layer is arranged on the outer surface of the base layer, and the friction layer comprises 60-95% silicon carbide, 5-40% silicon and 0-5% carbon. For example, the friction layer comprises 70% silicon carbide, 25% silicon and 5% carbon; or the friction layer comprises 80% silicon carbide, 16% silicon and 4% carbon; or the friction layer comprises 85% silicon carbide, 10% silicon and 5% carbon, etc. Irregular cracks are distributed on the surface of the friction layer, and adjacent cracks are interconnected to form crack units. The average longest distance of the crack unit in the plane direction is 3-7mm, and the average width of the crack unit perpendicular to the longest direction is 2.5-6.5mm. The crack distribution density ρ of the friction layer in any direction of the brake disc diameter, the crack distribution density ρ and the crack width w satisfy the following formula:

[0029]

[0030] Among them, ρ=n / L, n is the number of cracks passing through the length L in any direction, L is the radius of the brake disc, and α is the relationship coefficient, which can be any value between 2 and 8.

[0031] The silicon carbide in the friction layer includes first silicon carbide particles, second silicon carbide particles and third silicon carbide particles. The first silicon carbide particles have a particle size of 80-120 μm, the second silicon carbide particles have a particle size of 5-30 μm, and the third silicon carbide particles have a particle size of less than 5 μm.

[0032] The first silicon carbide particle content is 45-65% of the silicon carbide content, the second silicon carbide particle content is 20-40% of the silicon carbide content, and the third silicon carbide particle content is 10-20% of the silicon carbide content.

[0033] The average area of ​​the crack unit is 15-45mm 2 .

[0034] The matrix layer includes 30-50% carbon fiber, 40-65% silicon carbide and 5-15% silicon.

[0035] The present invention also provides a method for preparing a composite brake disc having a friction layer, comprising the following steps:

[0036] S1: preparing a carbon fiber preform of a predetermined thickness;

[0037] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body;

[0038] S3: Carbonizing the impregnated body to obtain a carbonized body, the carbonization temperature is 800-1100° C., and the temperature is kept for 4-6 hours;

[0039] S4: applying phenolic slurry containing silicon carbide powder on the carbonized body, and then drying to obtain a second body, wherein a prefabricated friction layer is formed on the surface of the second body, and the thickness of the prefabricated friction layer is 1-3 mm;

[0040] S5: subjecting the second green body to low-temperature graphitization treatment in nitrogen to obtain a graphitized green body;

[0041] S6: Mechanically processing the graphitized body to obtain a brake disc body;

[0042] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600-1700°C, the holding time is 2-4h, and the furnace pressure is less than 1000Pa;

[0043] S8: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the composite brake disc with the friction layer.

[0044] The method for preparing the carbon fiber preform comprises: stacking the carbon fiber unidirectional cloth and the carbon fiber web as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90 degrees, and after stacking one unit, acupuncture the sample, and repeating the above process to obtain a carbon fiber preform of a desired thickness, wherein the acupuncture density is 50-200 needles / cm 2 .

[0045] Step S2 and step S3 are performed at least once, so that the density of the carbonized body reaches 1.25-1.45 g / cm 3 .

[0046] The phenolic slurry comprises a silicon carbide particle concentration of 10-30wt%, a phenolic content of 5-25wt%, and an alcohol content of 50-85wt%; the particle size of the silicon carbide particles ranges from 20 to 150μm.

[0047] The low-temperature graphitization treatment temperature is 1400-1800° C. and the temperature is kept for 2 hours.

[0048] Example 1

[0049] This embodiment provides a composite brake disc having a friction layer. The steps of preparing the composite brake disc having a friction layer are as follows:

[0050] S1: Prepare a carbon fiber preform of a predetermined thickness, stack the carbon fiber unidirectional cloth and the carbon fiber mesh as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90°, and after stacking one unit, needle punch the sample, and repeat the above process to obtain a carbon fiber preform of a desired thickness, wherein the needle punching density is 150 needles / cm 2 ;

[0051] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body;

[0052] S3: The impregnated body is carbonized to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours. Steps S2 and S3 are performed at least once, and the carbonized body is impregnated again and then carbonized, and the process is repeated until the density of the carbonized body reaches 1.35 g / cm 3 ;

[0053] S4: brushing a phenolic slurry containing silicon carbide powder on the carbonized body, wherein the phenolic slurry comprises a silicon carbide particle concentration of 20wt%, a phenolic content of 10wt%, and an alcohol content of 70wt%; wherein the silicon carbide particles have a particle size of 100μm and account for 70% of the total mass of the silicon carbide particles, and the silicon carbide particles have a particle size of 20μm and account for 30% of the total mass of the silicon carbide particles; and then drying the body to obtain a second body, wherein a prefabricated friction layer is formed on the surface of the second body, and the thickness of the prefabricated friction layer is 1mm;

[0054] S5: subjecting the second green body to low-temperature graphitization treatment in nitrogen to obtain a graphitized green body, wherein the low-temperature graphitization treatment temperature is 1500° C. and the temperature is maintained for 2 hours;

[0055] S6: Mechanically processing the graphitized body to obtain a brake disc body;

[0056] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0057] S8: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the composite brake disc with the friction layer.

[0058] Example 2

[0059] This embodiment provides a composite brake disc having a friction layer. The steps of preparing the composite brake disc having a friction layer are as follows:

[0060] S1: Prepare a carbon fiber preform of a predetermined thickness, stack the carbon fiber unidirectional cloth and the carbon fiber mesh as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90°, and after stacking one unit, needle punch the sample, and repeat the above process to obtain a carbon fiber preform of a desired thickness, wherein the needle punching density is 150 needles / cm 2 ;

[0061] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body;

[0062] S3: The impregnated body is carbonized to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours. Steps S2 and S3 are performed at least once, and the carbonized body is impregnated again and then carbonized, and the process is repeated until the density of the carbonized body reaches 1.35 g / cm 3 ;

[0063] S4: applying phenolic slurry containing silicon carbide powder on the carbonized body, wherein the phenolic slurry comprises 20wt% of silicon carbide particles, 10wt% of phenolic content, and 70wt% of alcohol; wherein the silicon carbide particles have a particle size of 100μm and account for 80% of the total mass of the silicon carbide particles, and the silicon carbide particles have a particle size of 20μm and account for 20% of the total mass of the silicon carbide particles; and then drying to obtain a second body, wherein a prefabricated friction layer is formed on the surface of the second body, and the thickness of the prefabricated friction layer is 1mm;

[0064] S5: subjecting the second green body to low-temperature graphitization treatment in nitrogen to obtain a graphitized green body, wherein the low-temperature graphitization treatment temperature is 1500° C. and the temperature is maintained for 2 hours;

[0065] S6: Mechanically processing the graphitized body to obtain a brake disc body;

[0066] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0067] S8: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the composite brake disc with the friction layer.

[0068] Example 3

[0069] This embodiment provides a composite brake disc having a friction layer. The steps of preparing the composite brake disc having a friction layer are as follows:

[0070] S1: Prepare a carbon fiber preform of a predetermined thickness, stack the carbon fiber unidirectional cloth and the carbon fiber mesh as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90°, and after stacking one unit, needle punch the sample, and repeat the above process to obtain a carbon fiber preform of a desired thickness, wherein the needle punching density is 150 needles / cm 2 ;

[0071] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body;

[0072] S3: The impregnated body is carbonized to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours. Steps S2 and S3 are performed at least once, and the carbonized body is impregnated again and then carbonized, and the process is repeated until the density of the carbonized body reaches 1.35 g / cm 3 ;

[0073] S4: brushing a phenolic slurry containing silicon carbide powder on the carbonized body, wherein the phenolic slurry comprises a silicon carbide particle concentration of 20wt%, a phenolic content of 10wt%, and an alcohol content of 70wt%; wherein the silicon carbide particles have a particle size of 100μm and account for 60% of the total mass of the silicon carbide particles, and the silicon carbide particles have a particle size of 20μm and account for 40% of the total mass of the silicon carbide particles; and then drying to obtain a second body, wherein a prefabricated friction layer is formed on the surface of the second body, and the thickness of the prefabricated friction layer is 1mm;

[0074] S5: subjecting the second green body to low-temperature graphitization treatment in nitrogen to obtain a graphitized green body, wherein the low-temperature graphitization treatment temperature is 1500° C. and the temperature is maintained for 2 hours;

[0075] S6: Mechanically processing the graphitized body to obtain a brake disc body;

[0076] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0077] S8: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the composite brake disc with the friction layer.

[0078] Example 4

[0079] This embodiment provides a composite brake disc having a friction layer. The steps of preparing the composite brake disc having a friction layer are as follows:

[0080] S1: Prepare a carbon fiber preform of a predetermined thickness, stack the carbon fiber unidirectional cloth and the carbon fiber mesh as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90°, and after stacking one unit, needle punch the sample, and repeat the above process to obtain a carbon fiber preform of a desired thickness, wherein the needle punching density is 150 needles / cm 2 ;

[0081] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body;

[0082] S3: The impregnated body is carbonized to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours. Steps S2 and S3 are performed at least once, and the carbonized body is impregnated again and then carbonized, and the process is repeated until the density of the carbonized body reaches 1.35 g / cm 3 ;

[0083] S4: brushing a phenolic slurry containing silicon carbide powder on the carbonized body, wherein the phenolic slurry comprises a silicon carbide particle concentration of 20wt%, a phenolic content of 10wt%, and an alcohol content of 70wt%; wherein the silicon carbide particles have a particle size of 100μm and account for 70% of the total mass of the silicon carbide particles, and the silicon carbide particles have a particle size of 30μm and account for 30% of the total mass of the silicon carbide particles; and then drying to obtain a second body, wherein a prefabricated friction layer is formed on the surface of the second body, and the thickness of the prefabricated friction layer is 1mm;

[0084] S5: subjecting the second green body to low-temperature graphitization treatment in nitrogen to obtain a graphitized green body, wherein the low-temperature graphitization treatment temperature is 1500° C. and the temperature is maintained for 2 hours;

[0085] S6: Mechanically processing the graphitized body to obtain a brake disc body;

[0086] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0087] S8: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the composite brake disc with the friction layer.

[0088] Example 5

[0089] This embodiment provides a composite brake disc having a friction layer. The steps of preparing the composite brake disc having a friction layer are as follows:

[0090] S1: Prepare a carbon fiber preform of a predetermined thickness, stack the carbon fiber unidirectional cloth and the carbon fiber mesh as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90°, and after stacking one unit, needle punch the sample, and repeat the above process to obtain a carbon fiber preform of a desired thickness, wherein the needle punching density is 150 needles / cm 2 ;

[0091] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body;

[0092] S3: The impregnated body is carbonized to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours. Steps S2 and S3 are performed at least once, and the carbonized body is impregnated again and then carbonized, and the process is repeated until the density of the carbonized body reaches 1.35 g / cm 3 ;

[0093] S4: brushing a phenolic slurry containing silicon carbide powder on the carbonized body, wherein the phenolic slurry comprises a silicon carbide particle concentration of 20wt%, a phenolic content of 10wt%, and an alcohol content of 70wt%; wherein the silicon carbide particles have a particle size of 120μm and account for 70% of the total mass of the silicon carbide particles, and the silicon carbide particles have a particle size of 30μm and account for 30% of the total mass of the silicon carbide particles; and then drying the body to obtain a second body, wherein a prefabricated friction layer is formed on the surface of the second body, and the thickness of the prefabricated friction layer is 1mm;

[0094] S5: subjecting the second green body to low-temperature graphitization treatment in nitrogen to obtain a graphitized green body, wherein the low-temperature graphitization treatment temperature is 1500° C. and the temperature is maintained for 2 hours;

[0095] S6: Mechanically processing the graphitized body to obtain a brake disc body;

[0096] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0097] S8: grinding the surface of the siliconized body and processing the outer contour dimensions to obtain the composite brake disc with a friction layer

[0098] Comparative Example 1

[0099] This comparative example provides a composite brake disc having a friction layer, and the preparation steps of the composite brake disc having a friction layer are as follows:

[0100] S1: Prepare a carbon fiber preform of a predetermined thickness, stack the carbon fiber unidirectional cloth and the carbon fiber mesh as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90°, and after stacking one unit, needle punch the sample, and repeat the above process to obtain a carbon fiber preform of a desired thickness, wherein the needle punching density is 150 needles / cm 2 ;

[0101] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body;

[0102] S3: The impregnated body is carbonized to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours. Steps S2 and S3 are performed at least once, and the carbonized body is impregnated again and then carbonized, and the process is repeated until the density of the carbonized body reaches 1.35 g / cm 3 ;

[0103] S4: brushing a phenolic slurry containing silicon carbide powder on the carbonized body, wherein the phenolic slurry comprises 20wt% of silicon carbide particles, 10wt% of phenolic content, and 70wt% of alcohol; wherein the particle size of the silicon carbide particles is 100 μm; and then drying to obtain a second body, wherein a prefabricated friction layer is formed on the surface of the second body, and the thickness of the prefabricated friction layer is 1 mm;

[0104] S5: subjecting the second green body to low-temperature graphitization treatment in nitrogen to obtain a graphitized green body, wherein the low-temperature graphitization treatment temperature is 1500° C. and the temperature is maintained for 2 hours;

[0105] S6: Mechanically processing the graphitized body to obtain a brake disc body;

[0106] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0107] S8: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the composite brake disc with the friction layer.

[0108] Comparative Example 2

[0109] This comparative example provides a composite brake disc having a friction layer, and the preparation steps of the composite brake disc having a friction layer are as follows:

[0110] S1: Prepare a carbon fiber preform of a predetermined thickness, stack the carbon fiber unidirectional cloth and the carbon fiber mesh as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90°, and after stacking one unit, needle punch the sample, and repeat the above process to obtain a carbon fiber preform of a desired thickness, wherein the needle punching density is 150 needles / cm 2 ;

[0111] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body;

[0112] S3: The impregnated body is carbonized to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours. Steps S2 and S3 are performed at least once, and the carbonized body is impregnated again and then carbonized, and the process is repeated until the density of the carbonized body reaches 1.35 g / cm 3 ;

[0113] S4: applying phenolic slurry containing silicon carbide powder on the carbonized body, wherein the phenolic slurry comprises 20wt% of silicon carbide particles, 10wt% of phenolic content, and 70wt% of alcohol; wherein the particle size of the silicon carbide particles is 20μm; and then drying to obtain a second body, wherein a prefabricated friction layer is formed on the surface of the second body, and the thickness of the prefabricated friction layer is 1mm;

[0114] S5: subjecting the second green body to low-temperature graphitization treatment in nitrogen to obtain a graphitized green body, wherein the low-temperature graphitization treatment temperature is 1500° C. and the temperature is maintained for 2 hours;

[0115] S6: Mechanically processing the graphitized body to obtain a brake disc body;

[0116] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0117] S8: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the composite brake disc with the friction layer.

[0118] The composite brake discs with friction layers prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-2 were tested. The dynamic friction coefficient and wear rate of the carbon ceramic brake disc samples were tested using an MM-1000 friction tester. The effective friction surface of the test ring had an outer diameter of D75mm / inner diameter of D55mm×10mm, and a specific pressure of 98N / cm 2 , inertia is 3kgf·cm·s 2, linear speed is 25m / s.

[0119] The test data is shown in Table 1.

[0120] Table 1 Test data of composite brake discs with friction layers prepared in Examples 1-5 and Comparative Examples 1-2

[0121]

[0122] From the above examples and comparative data, it can be seen that as the content of 100μm silicon carbide added to the phenolic slurry increases, the wear rate begins to decrease and then increases. When the proportion of 100μm silicon carbide added increases from 60% to 70%, the content of coarse silicon carbide in the friction layer after siliconization increases, and the wear resistance improves; when the proportion of 100μm silicon carbide added increases from 70% to 80%, the proportion of small silicon carbide particles added decreases accordingly, the connection strength between silicon carbides decreases, and the wear amount increases instead. It can be seen from the data that by optimizing the size and addition amount of silicon carbide particles in the phenolic slurry, the crack width and crack density can be adjusted. Comparative Example 1 only adds 100μm silicon carbide particles, and the bonding strength between its silicon carbide particles decreases seriously, large particles of silicon carbide peel off, and the wear amount increases significantly; Comparative Example 2 only adds 20μm silicon carbide particles, and its silicon carbide particles are small and have poor wear resistance, so its wear amount is large. Moreover, the crack gaps are large, and the entire friction unit may peel off when worn.

[0123] The above disclosures are only several preferred embodiments of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the scope of the patent application of the present invention are still within the scope covered by the present invention.

Claims

1. A composite brake disc having a friction layer, characterized in that: The composite brake disc with a friction layer comprises a base layer and a friction layer, wherein the friction layer is arranged on the outer surface of the base layer, and the friction layer comprises 60-95% of silicon carbide, 5-40% of silicon and 0-5% of carbon; irregular cracks are distributed on the surface of the friction layer, and adjacent cracks are interconnected to form crack units, wherein the average longest distance of the crack units in the plane direction is 3-7 mm, and the average width of the crack units perpendicular to the longest direction is 2.5-6.5 mm; the crack distribution density ρ of the friction layer in any direction of the brake disc diameter and the crack width w satisfy the following formula: Among them, ρ=n / L, n is the number of cracks passing through the length L in any direction, L is the radius of the brake disc, and α is the relationship coefficient, which can be any value between 2 and 8.

2. The composite brake disc with a friction layer according to claim 1, characterized in that: The silicon carbide in the friction layer includes first silicon carbide particles, second silicon carbide particles and third silicon carbide particles. The first silicon carbide particles have a particle size of 80-120 μm, the second silicon carbide particles have a particle size of 5-30 μm, and the third silicon carbide particles have a particle size of less than 5 μm.

3. The composite brake disc with a friction layer according to claim 2, characterized in that: The first silicon carbide particle content is 45-65% of the silicon carbide content, the second silicon carbide particle content is 20-40% of the silicon carbide content, and the third silicon carbide particle content is 10-20% of the silicon carbide content.

4. The composite brake disc with a friction layer according to claim 1, characterized in that: The average area of ​​the crack unit is 15-45mm 2 .

5. The composite brake disc with a friction layer according to claim 1, characterized in that: The matrix layer includes 30-50% carbon fiber, 40-65% silicon carbide and 5-15% silicon.

6. A method for preparing a composite brake disc having a friction layer, for preparing a composite brake disc having a friction layer as claimed in any one of claims 1 to 5, characterized in that: The steps include: S1: preparing a carbon fiber preform of a predetermined thickness; S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body; S3: Carbonizing the impregnated body to obtain a carbonized body, the carbonization temperature is 800-1100° C., and the temperature is kept for 4-6 hours; S4: applying phenolic slurry containing silicon carbide powder on the carbonized body, and then drying to obtain a second body, wherein a prefabricated friction layer is formed on the surface of the second body, and the thickness of the prefabricated friction layer is 1-3 mm; S5: subjecting the second green body to low-temperature graphitization treatment in nitrogen to obtain a graphitized green body; S6: Mechanically processing the graphitized body to obtain a brake disc body; S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600-1700°C, the holding time is 2-4h, and the furnace pressure is less than 1000Pa; S8: performing surface grinding and outer contour dimension processing on the siliconized blank to obtain the composite brake disc with the friction layer.

7. The method for preparing a composite brake disc having a friction layer according to claim 6, characterized in that: The method for preparing the carbon fiber preform comprises: stacking the carbon fiber unidirectional cloth and the carbon fiber web as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90 degrees, and after stacking one unit, acupuncture the sample, and repeating the above process to obtain a carbon fiber preform of a desired thickness, wherein the acupuncture density is 50-200 needles / cm 2 .

8. The method for preparing a composite brake disc having a friction layer according to claim 6, characterized in that: Step S2 and step S3 are performed at least once, so that the density of the carbonized body reaches 1.25-1.45 g / cm 3 .

9. The method for preparing a composite brake disc having a friction layer according to claim 6, characterized in that: The phenolic slurry comprises a silicon carbide particle concentration of 10-30wt%, a phenolic content of 5-25wt%, and an alcohol content of 50-85wt%; the particle size of the silicon carbide particles ranges from 20 to 150μm.

10. The method for preparing a composite brake disc having a friction layer according to claim 6, characterized in that: The low-temperature graphitization treatment temperature is 1400-1800° C. and the temperature is kept for 2 hours.

Citation Information

Patent Citations

  • Carbon-ceramic brake disc with friction layer containing short fibers and preparation method of carbon-ceramic brake disc

    CN118622882A

  • Method for producing friction discs from fibre-reinforced ceramic materials

    EP2058546A2

  • Ceramic brake disc

    EP2918866A1